SISI Cerah Kepemimpinan: Menjelajahi Peran Humor dalam Menyeimbangkan Tuntutan Pekerjaan dan Keluarga di Universitas Lancang Kuning - Maherizal; Adi Rahmat; Fahmi Oemar; Didik Siswanto (Smart Education, 2026)
This study is motivated by the increasing work family conflict experienced by university lecturers due to high academic job demands. One leadership approach that is considered capable of alleviating this conflict is leadership humor. This research aims to examine the effect of positive leadership humor on work family conflict, with coworker socializing as a mediating variable among lecturers at Universitas Lancang Kuning. The study is grounded in the Stimulus Organism Response (SOR) theory and Conservation of Resources (COR) theory, which conceptualize leader humor as a social stimulus and a socioemotional resource. A quantitative approach with a causal research design was employed. Data were collected through structured questionnaires using a Likert scale from 186 lecturers selected through proportional stratified random sampling. Data analysis was conducted using Structural Equation Modeling Partial Least Squares (SEM-PLS). The findings indicate that positive leadership humor has a negative effect on work family conflict and a positive effect on coworker socializing. Furthermore, coworker socializing negatively affects work family conflict and significantly mediates the relationship between leadership humor and work family conflict. The study concludes that positive leadership humor plays a strategic role in fostering a supportive work environment and helping lecturers balance professional and family demands.